Electron Bernstein waves driven by electron crescents near the electron diffusion region - W. Y. Li (Nature Portfolio, 2020)
Various types of plasma waves are generated around electron diffusion regions (EDRs). Here the authors show electron Bernstein waves (EBWs), at the electron-scale boundary of the Hall current reversal near EDR, are sufficiently strong to diffuse electrons and modify electron pressure tensor.